Molly takes flight - Tripp, Valerie, 1951- (American girls collection., 1999)
Molly feels that everything in her life has changed when her father goes off to England to help wounded soldiers and her beloved aunt joins the Women's Airforce Service Pilots. Includes a section on women pilots in the armed services, and a project related to the story.